論傳統＂義＂德在抗擊重大疫情中的現實意義——基於博弈論的分析: On the Practical Dimension of the Traditional Chinese Concept of "Righteousness" in Fighting Against Covid-19 - An Analysis Based on Game Theory - KONG, Ying (International Journal of Chinese & Comparative Philosophy of Medicine, 2021)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 在中國發生重大的公共衛生危機——新型冠狀肺炎病毒爆發的背景下，防疫工作不可避免地面臨一些個人與他人或社會的利益衝突。妥善解決這些衝突需要道德的支撐。當前重大疫情下普通人表現出的助人為樂、捨己為人的義舉，或繼承自傳統美德，或至少與傳統“義”德相符合。傳統的“義”德注重公利，在抗擊重大疫情過程中能夠發揮重要作用。這種現實作用能夠被博弈論中的純策略博弈和信任博弈分析所證明。抗擊重大疫情需要整個社會的團結協作，個人需講求“公義”、 “信義”，明白義利的統一性，必要地讓渡“私利”，將防疫的“公利”最大化，方能打贏抗疫戰，從而更廣泛地保護個人“私利”。 In the context of the outbreak of covid-19 pandemic and its impact on public health, the conflicts of interests between individuals and between an individual and society have become an ethical challenge. The traditional Chinese concept of “righteousness” (yi) calls for the need for public good, whereas “benefit” (li) is often associated with private interests, as shown in the Confucian-Mohist debate. In this paper, I show that there is another reading of the concept of “righteousness” that does not necessarily exclude the idea of individual interest and benefit. In addition, I use “game theory” to illustrate the unity of public righteousness and private benefit.